Peças para pavimento intertravado de concreto: estudo de viabilidade técnica na incorporação de agregado reciclado - Leal, Cleber Eduardo Fernandes (2018)
As a major absorber of labor and inputs, the construction sector is responsible for significantly boosting a country's economy. On the other hand, due to this magnitude, the quantities of non-renewable natural resources consumed and waste generated by the civil construction industry have been alarming. With increasing generation, disposal areas are overloaded, and when they are not properly disposed of, waste can cause serious damage to the environment, health and public safety. Considering this concern, the present research had as main goal to analyze the technical feasibility in producing concrete paving blocks incorporating construction waste in the form of recycled aggregates. Recycled aggregates were collected at the São Carlos-SP and São José do Rio Preto-SP plants. Both were characterized as granulometry, unit weight, density, water absorption and powdery material. For the pieces manufacture, the recycled sand from Rio Preto was chosen, because it only contained concrete and mortar residues in its composition. It was defined 4 different mixes, counting with 0%, 10%, 20%, 30% of mass substitution of the natural sand by the recycled sand. The pieces were produced on an industrial scale and with the use of vibropress machine, in a partner factory of the study. After the production, the pieces were taken to the Brazilian Portland Cement Association, where they were evaluated at 7 and 28 days according to the compressive strength, splitting tensile strength, abrasion and water absorption. At 28 days, the mixes containing recycled aggregates provided satisfactory results and superior to the reference concrete. For compressive strength and splitting tensile strength, the best results were obtained with 20% of recycled sand, meeting the minimum limits required by Brazilian and British standards, respectively. All mixes met the abrasion limits proposed by the standards, with the lowest surface wear observed in the pieces with 10% of residue. For water absorption, the best results were provided by 10 and 20% substitution mixes. Only the mix with 30% absorbed water beyond the limit proposed in standard. The statistical analysis of the results showed that the replacement of natural sand by recycled sand at all levels did not significantly change the values of the properties of the pieces. Thus, it was concluded that the substitution of up to 30% of the natural sand content by recycled sand is, in fact, technically feasible, with a possible optimal substitution content between 20% and 30% or near theses limits.